Energy and Operating Costs of Methanol Fuel on A 4000 DWT Oil Chemical Tanker - Abyan Ariaputra Aziz; Fajri Ashfi Rayhan; Agus Dwy Bramastha; Muhammad Afrizal; Muhammad Sugeri; Amir Marasabessy (National Research and Innovation Agency (BRIN Publishing), 2024)
The International Maritime Organization (IMO) has introduced regulations that the shipping industry must reduce Greenhouse Gas Emissions by at least 50% by 2050 compared to 2008. At the same time, the IMO predicts that global shipping emissions will increase by 250% by 2050. Therefore, the Shipping Industry must fix this problem by reducing carbon emissions. Methanol Fuel is an alternative fuel for ships that is cost-effective, low-emission, environmentally friendly, and renewable. Methanol can reduce SOx emissions by up to 99%, NOx emissions by up to 60%, and Special Particulates by up to 95%. The purpose of this study is to make adjustments to the methanol-fueled main engine, calculate energy, operating costs, main engine retrofit prices, and return periods on the Oil Chemical Tanker 4000 DWT ship with the method of Round-Trip Shipping with Route Variations, Composition, and Fuel Prices. From the discussion of this study, it can be concluded that the calculation of energy and operating costs of Heavy Fuel Oil (HFO) and methanol is influenced by the amount of fuel used during the voyage, in addition to the results of the calculation of energy, operating costs, and retrofit prices on the Oil Chemical Tanker 4000 DWT (Deadweight Tonnage) ship with a voyage on the American route of 3,467,320 MJ, Rp. 1,565,684,341.-, and a 2.4-year return period, the European route of 3,137,099 MJ, Rp. 1,352,844,897.-, and 2.8 years of return period, and Asia Pacific routes of 3,274,914 MJ, Rp. 1,069,629,506.-, and 3.5 years of return period, as well as the price of the main engine retrofit, which reached Rp. 7,574,435,035.-. These findings offer valuable insights for shipping companies to make informed decisions about fuel selection and retrofit investments, potentially leading to significant cost savings and a reduced environmental footprint. Furthermore, the study provides a strategic foundation for complying with IMO regulations and achieving long-term sustainability goals in the maritime industry.